Forensic Entomology and the importance of entomological collections - Verdi , Jordana (2023)
Entomological collections represent fundamental tools in the study and correct recognition of taxons, recording the species and their geographic distribution, helping in the elaboration of publications destined to the identification of insect groups, development of different technical works and extension activities. The collections stand out as a basis for the studies of biodiversity and evolution, in addition to being invaluable for both researchers and society in general. When well maintained and organized, including a suitable environment and correct management, entomological collections can last for years and thus are extremely important for research. Although the great technological advance that helps in the identification of taxons, the use of collections in routine species identification activities is still necessary. Thus, the present work aimed to carry out a literature review on the importance of entomological collections in the identification of species and application of Forensic Entomology in criminal expertise. With the advancement of forensic studies, the importance of entomological collections was verified, as they help in the identification of insects that visit the corpse, facilitating forensic analysis and contributing data in an investigation.